2014
DOI: 10.1371/journal.pone.0086239
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Long-Term Efficacy of Lopinavir/Ritonavir and Similar Drug-Resistance Profiles in Different HIV-1 Subtypes

Abstract: BackgroundAnalysis of potentially different impact of Lopinavir/Ritonavir (LPV/r) on non-B subtypes is confounded by dissimilarities in the conditions existing in different countries. We retrospectively compared its impact on populations infected with subtypes B and C in Israel, where patients infected with different subtypes receive the same treatment.MethodsClinical and demographic data were reported by physicians. Resistance was tested after treatment failure. Statistical analyses were conducted using SPSS.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 65 publications
5
9
0
Order By: Relevance
“…We use the H-CBN2 method to infer evolutionary pathways to lopinavir resistance in HIV-1 subtypes B and C confirming previous knowledge on frequently observed patterns of resistance-conferring mutations in response to lopinavir treatment [33,34].…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…We use the H-CBN2 method to infer evolutionary pathways to lopinavir resistance in HIV-1 subtypes B and C confirming previous knowledge on frequently observed patterns of resistance-conferring mutations in response to lopinavir treatment [33,34].…”
Section: Introductionsupporting
confidence: 67%
“…For subtype B, we find strong support for a mutation at residue 46 as an initial event ( Fig 6). The inferred posets can explain previously observed mutation patterns, such as M46I+I54V alone or in combinations with L76V or V82A in subtype B [33], as well as M46I+I54V+V82A and L10F+M46I+I54V+L76V+V82A in subtype C [34].…”
Section: Comparison Of Drug Resistance-associated Mutational Pathwayssupporting
confidence: 60%
See 1 more Smart Citation
“…Although differences in drug susceptibility exist between subtypes, recent large international studies assessing effectiveness of various ART regimens have not demonstrated increased treatment failures in specific subtypes, although there have been instances of delayed CD4 cell count recovery [ 33 , 34 , 35 , 36 ] attributed to viral subtype. For instance, in a study conducted across Thailand, Hong Kong, Japan, Taiwan, and South Korea, 1036 individuals, of whom 778 harbored CRF01_AE virus and 258 individuals harbored sub-type B, were followed for 1547 person-years.…”
Section: Effect Of Hiv Subtypes On Antiretroviral Therapy Outcomesmentioning
confidence: 99%
“…There was no difference in virologic response between subtypes. In a study from Israel, the authors noted that the perceived differences in treatment outcomes amongst various subtypes might actually be due to differences in quality of care provided across economic and geographic boundaries [ 33 ]. In their population, they showed that although there was a significant difference in rise of CD4 count by subtype, (175 in subtype B versus 98 in subtype C, p < 0.001), no such difference existed in viral loads or resistance rates.…”
Section: Effect Of Hiv Subtypes On Antiretroviral Therapy Outcomesmentioning
confidence: 99%